Pendampingan dan Penyuluhan Pembuatan Pojok Baca untuk Mendukung Literasi Baca-Tulis di SD Negeri 117509 Poldung - Nurlina Ariani Hrp; Indah Fitria Rahma; Siti Zahara Saragih; Siti Suharni Simamora; Lily Rohanita Hasibuan; Novi Fitriandika Sari; Dwi Yuliana; Hotna Sarida Harahap; Rahmi Nazliah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
This Community Service activity aims to improve the implementation and fluency of students and schools in carrying out reading and writing literacy at SD Negeri 117509 Poldung schools. One of the schools that is far from urban areas and there is no internet access that supports it. Based on the background of the school, which is a public school located in a village with a small population and lack of adequate learning media to use, it results in the ineffectiveness of government programs for reading literacy activities to be carried out optimally. Activities in this community service program are carried out by Labuhanbatu University lecturers and students as a form of participation to improve education in Indonesia. The form of activity is to provide counseling and assistance in making reading corners and increasing students' reading interest as a form of reading literacy. This activity is considered to be able to increase students' interest in reading and will significantly increase students' literacy activities at the school.